2013
DOI: 10.1007/s00705-013-1728-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of TaqMan-based qPCR method for detection of caprine arthritis–encephalitis virus (CAEV) infection

Abstract: A specific and sensitive two-step TaqMan real-time PCR has been developed for rapid diagnosis of caprine arthritis-encephalitis virus (CAEV) infection by using a set of specific primers and a TaqMan probe targeting a highly conserved region within the gene encoding the viral capsid protein (CA). The assay successfully detected CAEV proviral DNA in total DNA extracts originating from cell culture, whole blood samples and isolated PBMCs, with a lower detection limit of 102 copies and a linear dynamic range of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Moreover, due to advancement in the polymerase chain reaction (PCR) technology, there has been enormous improvement in the diagnosis of respiratory diseases of small ruminants [25]. Recent advances in biotechnology and molecular biology have led to the development of a variety of diagnostic assays, namely, PCR, RT-PCR, PCR-ELISA, RAPD, AFLP, RFLP, real-time PCR, quantitative PCR, multiplex PCR, LAMP, microsatellites, gene sequencing, and phylogenetic analysis, which not only help in identification but also assist in molecular characterization of various pathogens [20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Various conventional diagnostic tests, namely, isolation, postmortem finding, and gross clinical examinations along with modernized serological and molecular tests, are enlisted in Figure 1.…”
Section: Need Of Advanced Diagnostic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, due to advancement in the polymerase chain reaction (PCR) technology, there has been enormous improvement in the diagnosis of respiratory diseases of small ruminants [25]. Recent advances in biotechnology and molecular biology have led to the development of a variety of diagnostic assays, namely, PCR, RT-PCR, PCR-ELISA, RAPD, AFLP, RFLP, real-time PCR, quantitative PCR, multiplex PCR, LAMP, microsatellites, gene sequencing, and phylogenetic analysis, which not only help in identification but also assist in molecular characterization of various pathogens [20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Various conventional diagnostic tests, namely, isolation, postmortem finding, and gross clinical examinations along with modernized serological and molecular tests, are enlisted in Figure 1.…”
Section: Need Of Advanced Diagnostic Approachesmentioning
confidence: 99%
“…This type of PCR assay especially provides a useful method to detect CAEV infection in goats [ 66 68 ]. A two-step TaqMan quantitative (q) PCR, which is specific as well as sensitive for the detection of infection due to CAEV by the use of a set of primers (specific), and a TaqMan probe that targets a region which is highly conserved within the gene that encodes the capsid protein of the virus have been developed [ 33 ]. In the total deoxyribonucleotide (DNA) extracts, the proviral DNA can be detected successfully by this assay.…”
Section: Advances In Diagnosis Of Respiratory Diseases Of Small Rumentioning
confidence: 99%
See 1 more Smart Citation
“…Several real time PCR assays for SRLV detection have also been published [8,21-23], but to our knowledge only four real time PCR assays for diagnostic purposes have been described to date [24-27]. …”
Section: Discussionmentioning
confidence: 99%
“…Ciglenecki et al (2008) reported that the one-step real-time TaqMan RT-PCR assay was more appropriate for pestivirus quantification that reduces the risk of contamination and is less time consuming as compared to the conventional PCR. A TaqMan-based real-time PCR assay was also devised for the detection of porcine circovirus type 2 (Zhao et al, 2010), porcine boca-like virus (Li et al, 2011), caprine arthritisencephalitis virus (Li et al, 2013) and porcine parvovirus (Song et al, 2010;Gava et al, 2015).…”
Section: Resultsmentioning
confidence: 99%